Long-term pain caused by obturation material pushed beyond the apex – a case report - Olborska, Anna; Osica, Piotr; Janas-Naze, Anna (Journal of Education, Health and Sport, 2018)
The article presents a case of pain sensation caused by obturation material, pushed beyond the radiological apex of maxillary premolar, as a iatrogenic error of endodontic treatment and not removing the material during tooth extraction.